Penanaman Nilai-Nilai Ketauhidan Anak Usia Dini Melalui Pembelajaran Sholat di RA Masyithoh II Ropoh Kecamatan Kepil Kabupaten Wonosobo Jawa Tengah Tahun 2023/2024 - Baiti , Frisca Adina Nur Hana Halatul (Literasi: Jurnal Pendidikan Guru Indonesia, 2024)
This aims to: 1) To find out about instilling the values of monotheism in early childhood through learning to pray at RA Masyithoh II Ropoh. 2) To determine the supporting and inhibiting factors in prayer learning towards instilling the values of monotheism in early childhood at RA Masyithoh II Ropoh. This type of research uses qualitative research. Data collection techniques use interview methods, observation, documentation after the data is collected, and analyzed using data collection, data reduction, data presentation. Based on this research, it can be concluded that: 1) Instilling the values of monotheism through early childhood prayer learning at RA Masyithoh II Ropoh teaches children several values. Children know the value of tawakal through the takbiratul ihram movement, children know the cognitive value through memorizing Surah Al-Fatihah and prayer prayers, children know the noble value through the movement of placing both hands on the chest (crossing their arms), children know the value of tawadhu' through the bowing movement, children get to know the value of self-confidence through the movement of getting up from bowing down, children get to know the value of love through the prostrate movement, children get to know the value of steadfastness through the iftirasy movement, and children get to know the value of hablumminannas hablumminallah through the greeting movement. 2) Supporting and inhibiting factors relate to the role of teachers and guardians of students, as well as the participation and willingness of children in instilling the values of monotheism through prayer learning at RA Masyithoh II Ropoh. In terms of supporting factors, the teacher is able to guide and organize the activities, the student's guardian helps the child prepare the attributes for implementing prayer learning to be taken to school, the child plays a role with enthusiasm in the activity. Inhibiting factors, teachers may have limited knowledge and lack of understanding of the value of monotheism, the response of parents, who are not used to inviting children to prayer activities or do not appreciate the importance of the value of monotheism, some children also tend not to be interested in prayer learning activities.